Case report: Primary myelofibrosis presenting with portal hypertension mimicking cirrhosis - Gan, Xiayu; Yu, Shengjie; Zhu, Min; Ning, Bo; He, Song; Xie, Xiaoyue; Tu, Linshuang; Yu, Huihong (Frontiers in Medicine, 2024)
Primary myelofibrosis (PMF) is an infrequent etiology of noncirrhotic portal hypertension (PH). In clinical settings, non-cirrhotic PH is often misdiagnosed as cirrhotic PH. This case report details a patient who exhibited recurrent esophageal variceal hemorrhage and was initially misdiagnosed with cirrhosis. Initially poised for liver transplantation, the patient’s liver biopsy revealed no significant cirrhosis but showed signs of extramedullary hematopoiesis (EMH). Following the accurate diagnosis of PMF, the patient underwent standard treatment, leading to an absence of recurrent gastrointestinal hemorrhage due to esophageal varices for nearly three years.